ESTUDIO COMPARATIVO DEL SISTEMA INFORMÁTICO DE COMPRA Y VENTA DE PRODUCTOS DE LA EMPRESA "WIL MARKET" Y LOS SISTEMAS DE INFORMACIÓN GERENCIAL. - CABALLERO TORRES, CRISTOBAL JARDEL (2019)
The "Wil Market" supermarket is one of the largest food distribution centers of the Pueblo Nuevo site, opened in 2012 with a small commercial space dedicated only to the sale of pulses, but due to the great reception, its owners decided to expand their offer with products of first necessity, over the years it has been progressing through the years, at the same time that it has multiplied considerably its clientele, portfolio of products offered to the community, characterization to maintain the best market prices and a comfortable area for customer satisfaction. The purpose of this case is to make a comparison between the information system that is implemented in the supermarket "Wil Market" in front of the management information systems, in such a way that the supermarket "Dismero" is taken as reference to make the comparison based on the processes that its managerial information system incorporates, since it is one of the supermarkets that handles large volumes of information so it has chosen to use this type of information system, in addition it shares the same commercial purposes that is marketing of products of first necessity. The research subline that governs this document is the development of computer systems applied to the software and programming area, since Management Information Systems stand out in providing managers of all grades and all positions with relevant information, becoming complementary in the activities that are carried out in the organization, in order to grant the possibility of making effective and timely decisions in the planning, direction and control of the activities for which they are consistent.